Diversity and bioactivity of bacterial endophyte community of Cupressaceae. Issue 4 (9th March 2016) - Soltani, J.; Zaheri‐Shoja, M.; Hamzei, J.; Hosseyni‐Moghaddam, M. S.; Pakvaz, S.
Summary: The plant family Cupressaceae (Coniferales) harbours diverse endophytic fungi with antifungal, antibacterial and antiproliferative activities. Here, endophytic association of a broad bacterial community with the healthy foliar tissues of Cupressus arizonica, Cupressus sempervirens, Juniperus communis and Thuja orientalis (Cupressaceae) is shown. We isolated over 69 endophytic bacterial strains of Proteobacteria, Bacilli and Actinobacteria from Cupressaceae. The initial screening for antifungal activity against Pyricularia oryzae identified eleven superior bacterial strains which were identified as Brevundimonas diminuta CAE24 (G −, Caulobacteraceae, Alphaproteobacteria); Stenotrophomonas maltophilia CAE23, CSE4, CSE12, CSE42, CSE49 and CSE62 (G −, Xanthomonadaceae, Gammaproteobacteria); Bacillus pumilus CSE66 and Bacillus subtilis POE26 (G +, Bacillaceae, Bacilli); and Microbacterium resistens CSE19 (G +, Microbacteriaceae, Actinobacteria). The dominant isolated bacterial species was S. maltophilia . This species represented 63.6% of the superior strains which was ubiquitous and also non‐host specific. In addition, the superior bacterial strains produced bioactive secondary metabolites and volatile compounds (VOCs) with antifungal activity against the fungal pathogens of Cupressaceae, that is Diplodia seriata, Phaeobotryon cupressi and Spencermartinsia viticola . The antagonistic activity of the endophytic bacteria on the target fungi was also confirmed in vitro . To our knowledge, this is the first to document such an endophytic bacterial community in Cupressaceae and its bioactivity. These findings may find application in organic agroforestry for plant disease biocontrol and in biopharmacy for lead molecule discovery.